2017
DOI: 10.1007/s00296-017-3836-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum serotonin levels and bone in rheumatoid arthritis patients

Abstract: In rheumatoid arthritis (RA), a disease characterized by bone loss, increased levels of serotonin have been reported. Recent studies have demonstrated a role for circulating serotonin as a regulator of osteoblastogenesis, inhibiting bone formation. Thus, we measured serum serotonin levels (SSL) in a Portuguese sample of 205 RA patients and related these to anthropometric variables, disease parameters, serum bone biomarkers, and bone mineral density (BMD) assessed by dual-energy X-ray absorptiometry at several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
2
9
1
Order By: Relevance
“…RA is a chronic autoimmune inflammatory disease with typical characteristics of chronic inflammation and joint damage (71). Activated platelets and increased serum levels of 5-HT have been reported; high levels may be a negative predictor of bone mineral density in RA for suppressing osteoblasts (72). It has been demonstrated that 5-HT activates 5-HT 1B receptors on osteoblasts and inhibits their proliferation by activating proteinkinase A and cAMP-response element binding protein signaling pathway (73).…”
Section: Rheumatic Diseases Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…RA is a chronic autoimmune inflammatory disease with typical characteristics of chronic inflammation and joint damage (71). Activated platelets and increased serum levels of 5-HT have been reported; high levels may be a negative predictor of bone mineral density in RA for suppressing osteoblasts (72). It has been demonstrated that 5-HT activates 5-HT 1B receptors on osteoblasts and inhibits their proliferation by activating proteinkinase A and cAMP-response element binding protein signaling pathway (73).…”
Section: Rheumatic Diseases Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…In RA patients, increased levels of circulating serotonin, possibly released by activated platelets, have been reported. In the authors’ opinion, this finding may represent a negative predictor of bone mineral density in RA associated with a suppression of osteoblasts [ 64 , 65 ]. Serotonin levels are also elevated in RA SFs, where it induces synovial plasma extravasation via the release of inflammatory mediators [ 66 , 67 ].…”
Section: Tryptophan Metabolism and Ramentioning
confidence: 99%
“…Hypertension was defined as systolic blood pressure ≥ 140 mm Hg, diastolic blood pressure ≥ 90 mm Hg or taking antihypertensive medication, dyslipidemia as total cholesterol ≥ 200 mg/dL or taking antidyslipidemic agents, diabetes as a fasting glucose ≥ 126 mg/dL or taking hypoglycemic agents . The included population integrates a larger group already characterized in terms of myocardial perfusion scintigraphy as well as circulating serotonin levels and LRP5 polymorphisms . The selection of patients for this specific study was purely based on equipment availability and conducted regardless of patient characteristics.…”
Section: Methodsmentioning
confidence: 99%